2012
DOI: 10.1128/iai.05845-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expression of Helicobacter pylori Virulence Genes in Patients with Gastritis, Ulcer, and Gastric Cancer

Abstract: The best-studied Helicobacter pylori virulence factor associated with development of peptic ulcer disease or gastric cancer (GC) rather than asymptomatic nonatrophic gastritis (NAG) is the cag pathogenicity island (cagPAI), which encodes a type IV secretion system (T4SS) that injects the CagA oncoprotein into host epithelial cells. Here we used real-time reverse transcription-PCR (RT-PCR) to measure the in vivo expression of genes on the cagPAI and of other virulence genes in patients with NAG, duodenal ulcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…. It was also shown that in vivo expression of CagA in gastric biopsies was lower than its in vitro expression which was further consistent with a DNA microarray study wherein the in vivo CagA expression was downregulated by low pH levels .…”
Section: Discussionsupporting
confidence: 84%
“…. It was also shown that in vivo expression of CagA in gastric biopsies was lower than its in vitro expression which was further consistent with a DNA microarray study wherein the in vivo CagA expression was downregulated by low pH levels .…”
Section: Discussionsupporting
confidence: 84%
“…A recent study found vacA expression to be higher in patients with gastric cancer than in those with non-atrophic gastritis or duodenal ulcer 25. This agrees with our finding that higher vacA expression in the gastric mucosa is associated with increased inflammation and the presence of atrophy.…”
Section: Discussionsupporting
confidence: 93%
“…Helicobacter pylori infection is found in approximately 50% of the world's population and provokes chronic inflammation which can further cause peptic ulcer disease (10-15%) and gastric cancer (1-3%) [1]. Recently, H. pylori infection has been found to be a major risk factor for peptic ulcer disease (PUD), including gastric and duodenal ulcers [2].…”
Section: Introductionmentioning
confidence: 99%